965 Airway Skills in Paediatric Critical Care Units; a National Survey of Non-Anaesthetic Trainees. (October 2012) - Murray, F; Vaidya, M; Clifton, B
Abstract : Background: Airway interventions in critically ill patients are associated with a higher incidence of complications; inadequate skill can have serious implications. We conducted a survey to investigate airway skills training of non-anaesthetic trainees working in PICU in the UK and Ireland and to assess the need for an airway skills course specifically for these trainees. Methods: A survey was emailed to PICUs listed on the Paediatric Intensive Care Audit Network requesting completion by non-anaesthetic trainees. Results: Of 25 units eligible, 14 confirmed participation (53%). Sixty-five trainees responded. Most were of a paediatric background and of ST5 level and above. Only 48% received airway training on induction to PICU. This comprised of bag-mask ventilation (100%), airway adjuncts (71%), laryngeal masks (48%), intubation (74%), and emergency cricothyroidotomy (19%). Previous training came from advanced paediatric life support (APLS), neonatal intensive care, in-house resuscitation training or anaesthetic modules. Emergency airway scenarios were encountered by 90% and included accidental extubations, blocked or dislodged endotracheal and tracheostomy tubes, respiratory arrests and upper airway obstruction. Of these only 64% felt they had sufficient training to manage the situation as the first attending doctor. Availability of an airway skills course was supported by 83%. Comments highlighted the importance placed on dedicated theatre time. Conclusions: The percentage of trainees who encountered emergency airway scenarios illustrates the importance of basic airway skills. However only 48% of trainees received airway training on induction to PICU. The numbers in favour of an airway course could indicate a current gap in training.